Media Representations of the Egyptian Military Overturn: A Multimodal Analysis of Online News Articles of the New York Times and the Hindustan Times - Pokharel, Khem Raj (My University, 2014)
The military overturn which happened on 3rd July, 2013 in Egypt astonished the democratic nations because Egypt had lost the officially elected president Mohammed Morsi from the Islamic Brotherhood Party. Many international and national media gave live casts of the events with the help of their agencies and sources. On 14th August, there was a huge massacre. Many supporters of Morsi (mostly Islamists), neutral civilians, security personae and foreigners were killed, wounded and hospitalized. Online media represented the Egyptian events with the usage of multiple modes: visual and verbal. This study explores the online news articles of the New York Times and the Hindustan Times on the Egyptian events during the period of 15th to 19th August, 2013. Adopting a multimodal discourse analysis approach, as developed in the tradition of systemic functional grammar, the study analyzes how social actors are represented in the news articles. This analysis is based on both visual and verbal representations and shows the probable relationships among visual and verbal representations of social actors and the readers. The analysis shows that the articles from different media houses give importance to different social actors and represent them according to their interests. The study also shows that the media represent more internal social actors than external social actors if the events are recent. But, on the other hand, if the events are equilibrated, the online news represent more external social actors than internal ones.
Keywords: Communication; Media; Multimodality; Critical Discourse Analysis; Social Actors; New York Times; Hindustan Times; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|